Coastal area governance system in Japan resources, legal framework and strategies - Fernandez, Pepito R., Jr (Danyag : Journal of Humanities and Social Sciences, 1999)
Successful coastal management and development require an access to, and accurate use of, social, economic, spatial, and environmental database that integrates scientific and local knowledge systems. In addition to contributing to the understanding of the environment and the potential impacts of development, the compilation of an inventory of essential data also ensures a common information base for all decision makers so that misinformation and individual perceptions from which conflicts may arise can be avoided. But often missing in the inventory of useful data is information on the governance framework of coastal management systems. This paper provides an inventory and analysis of the coastal area governance system (CAGS) of Japan using content analysis of key documents and limited field observations and interviews. The CAGS is described and analyzed in terms of its resources, legal structure, and strategies. Key issues are then raised regarding the promotion of sustainable coastal area development (increased production coupled with resource protection/ conservation and social equity) in Japan.